2020
DOI: 10.3390/f11090957
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Radionuclides in the Trees of Fukushima Forests 4. Binding of Radioiodine to Xyloglucan

Abstract: The 1,4-linked glucans such as xyloglucan and amylose are known to form a complex with iodine/iodide ions and to also be precipitated with CaCl2 in the presence of iodine. Here, we show that iodine gas could be specifically incorporated into xyloglucan. Furthermore, we show that [125I]I2 gas is, over time, incorporated at high levels into the entire outer surface of poplar seedlings but that spraying seedlings with abscisic acid to close stomata decreases the incorporation of the gas. There was less incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Here, we showed that radioiodine-targeted xyloglucan was elevated in the annual rings of forest trees after a megathrust earthquake (Figure 2). Therefore, we conclude that the increased xyloglucan signals that we observed in the growth rings of forest tree trunks in the wild were likely caused, at least in part, by earthquakes, different from the intake of radionuclide in the trees due to the accident involving a nuclear power plant [1][2][3][4]. The 2011 megathrust earthquake not only triggered a nuclear power plant accident that dispersed radioiodine, which then became bound to xyloglucan in trees as an artificial event due to a human error, but also increased xyloglucan signaling in annual rings of forest trees as a plant response against seismic stress under natural phenomena.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Here, we showed that radioiodine-targeted xyloglucan was elevated in the annual rings of forest trees after a megathrust earthquake (Figure 2). Therefore, we conclude that the increased xyloglucan signals that we observed in the growth rings of forest tree trunks in the wild were likely caused, at least in part, by earthquakes, different from the intake of radionuclide in the trees due to the accident involving a nuclear power plant [1][2][3][4]. The 2011 megathrust earthquake not only triggered a nuclear power plant accident that dispersed radioiodine, which then became bound to xyloglucan in trees as an artificial event due to a human error, but also increased xyloglucan signaling in annual rings of forest trees as a plant response against seismic stress under natural phenomena.…”
Section: Discussionmentioning
confidence: 75%
“…The earthquake and tsunami on 11 March 2011 led to a meltdown followed by a hydrogen explosion at the Fukushima-Daiichi nuclear power plant in Japan, causing the dispersal of abundant radionuclides into forests and local residences by gaseous or aerosol forms [1][2][3][4]. Radioiodine and radiocesium were likely incorporated and fixed in forest trees.…”
Section: Introductionmentioning
confidence: 99%